EXPLORING THE EFFECTIVENESS OF SOLUTION-FOCUSED BRIEF COUNSELING IN EDUCATION: A LITERATURE REVIEW - Zahratunni’am (CV. TOTUS TUUS, 2024)
Counseling is a profession witnessing significant growth in America, responding to human needs since ancient times. Post-modern counseling, influenced by social constructivism, emphasizes the relativity of truth and reality. Solution-Focused Brief Counseling (SFBC), rooted in the counselor's strengths and focusing on future solutions, emerges as a potent approach. This paper explores the effectiveness of SFBC in education, particularly in addressing student issues. A literature study was conducted to gather data on the effectiveness of SFBC counseling in education. Data collection involved reviewing relevant articles and journals, totaling 20 sources. Content analysis was employed to interpret the findings. SFBC counseling demonstrated efficacy across various student issues, including self-esteem, self-control, academic procrastination, and truancy. Techniques like pre-test-post-test designs, group counseling, and individual counseling via video calls were utilized. The scope ranged from middle school to college, with adolescents being the primary demographic. Recommendations for future research include further exploration of SFBC's potential and its integration into school counseling programs. SFBC counseling has shown promising results in addressing student issues and promoting well-being. Its diverse applications and techniques underscore its potential for enhancing educational outcomes. Integration into school counseling services could further support students' holistic development and academic success.